Reduced serum club cell protein as a pulmonary damage marker for chronic fine particulate matter exposure in Chinese population. (March 2018) - Wang, Yanhua; Duan, Huawei; Meng, Tao; Shen, Meili; Ji, Qianpeng; Xing, Jie; Wang, Qingrong; Wang, Ting; Niu, Yong; Yu, Tao; Liu, Zhong; Jia, Hongbing; et al.
Abstract: Background: Exposure to fine particulate matter (PM2.5 ) pollution is associated with increased morbidity and mortality from respiratory diseases. However, few population-based studies have been conducted to assess the alterations in circulating pulmonary proteins due to long-term PM2.5 exposure. Methods: We designed a two-stage study. In the first stage (training set), we assessed the associations between PM2.5 exposure and levels of pulmonary damage markers (CC16, SP-A and SP-D) and lung function in a coke oven emission (COE) cohort with 558 coke plant workers and 210 controls. In the second stage (validation set), significant initial findings were validated by an independent diesel engine exhaust (DEE) cohort with 50 DEE exposed workers and 50 controls. Results: Serum CC16 levels decreased in a dose response manner in association with both external and internal PM2.5 exposures in the two cohorts. In the training set, serum CC16 levels decreased with increasing duration of occupational PM2.5 exposure history. An interquartile range (IQR) (122.0 μg/m 3 ) increase in PM2.5 was associated with a 5.76% decrease in serum CC16 levels, whereas an IQR (1.06 μmol/mol creatinine) increase in urinary 1-hydroxypyrene (1-OHP) concentration was associated with a 5.36% decrease in serum CC16 levels in the COE cohort. In the validation set, the concentration of serum CC16 in the PM2.5 exposed group was 22.42% lower than that of the controls and an IQR (1.24 μmol/mol creatinine) increase in urinary 1-OHP concentration was associated with a 12.24% decrease in serum CC16 levels in the DEE cohort. Conclusions: Serum CC16 levels may be a sensitive marker for pulmonary damage in populations with high PM2.5 exposure. Highlights: A two-stage design assessed the effect of ambient PM2.5 on serum pulmonary markers. Ambient PM2.5 was associated with lower CC16 by impairing club cells in the lungs. Cigarette smoking was associated with serum CC16 independent of PM2.5 exposure. Low serum CC16 concentration was associated with lung function impairment.